OPTIMIZATION OF THE MULTIDOOR APPROACH IMPLEMENTATION IN HANDLING CRIMINAL CASES IN THE ENVIRONMENTAL FIELD - Natalia, Indriyane Vera; Priyanta, Maret (Tadulako University, 2020)
Criminal acts in the environmental field are cross sectoral because they are almost followed by other criminal acts such as money laundering, bribery, corruption, gratification, etc. Thus, a multidoor approach was appear with the aim that the limitations of one rule can be filled with another. Furthermore, the magnitude of the chances of escape from criminal offenses, the ineffectiveness of environmental recovery, and the unavailability of deterrent effects can be avoided. The multidoor approach is a legal approach that relies on various laws to ensnare perpetrators of criminal acts in the environmental field. However, until now the application of the multidoor approach has not shown significant results. In this research, the concept of the multidoor approach will be examined from the background of its emerge, its type, and the legal instruments that govern it to its application as well as efforts to optimize the application of the multidoor approach. This research is a normative legal research through the method of legislation approach, conceptual approach and analytical approach. The research specification is analytical descriptive. The object of normative legal research is in the form of qualitative legal material, namely primary legal material, namely legislation and secondary legal material, namely library material. With regard to research data, both secondary and primary data, qualitative juridical analysis is carried out using legal interpretation methods. The conclusion of this study is to provide an understanding of the concept of the multidoor approach and provide suggestions for optimizing the application of this approach.